Word-formation of epithets and names in Indo-Iranian in their relationship with underlying syntax, ritual phraseology and poetical idiomatics - Sadovski, Velizar (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2024)
The present article demonstrates systematic correspondences between nominal compounds and derivatives, on the one hand, and syntactic structures and phraseological collocations, on the other, in the Veda and the Avesta and argues in favour of their common Indo-Iranian background. Part 1 shows that an Old Iran. personal name attested in Elamite transmission from Persepolis comes from an IIr. *Hr̥ta-mi(H)azdʰHa- and points out that this compound consists of an anterior member IIr. *Hr̥ta- ‘Rightness’ and a posterior term *mi(H)azdʰHa- ‘(solid) meal offering’, also occurring in formations like Young Avestan (*)Nərə-miiazda- (discussed in Part 3) and Old Iran. *Dāma-mii̯azda- (Part 4). The term *mi(H)az-dʰHa- itself consists of two compositional members and is analyzed as a desyntagmatic nomen actionis that ultimately goes back to a factitive verbal phrase. Valuable for its interpretation are syntagmata attested in Old and Young Avestan: Part 2 discovers important formulaic collocations in which lexemes like IIr. *Hr̥ta- ‘Rightness’ and *mi(H)az-dʰHa- occur together in the Avestan liturgy and in parallels from the Vedic ritual. Elements of such collocations in the Gāϑās – Av. aṣ̌a-, nəmah-, myazda- but also nar- and dāman- / root DĀ – fully correspond to the Old Indic terms r̥tá-, námas-, miyédha- but also nár- and dhā́man- / root DʰĀ; they are attested in further compounds, e.g. Old Iran. *(H)r̥ta-dʰāma- (Part 5). The added value of these lexical constellations is in their joint occurrence in nominal compounds and in phraseological structures; the five parts of the article display the role of such formulaic collocations for the reconstruction of the Indo-Iranian lexicon, word formation but also ritual poetry and practice.